Effect of Triple Combination Therapy With Lopinavir-Ritonavir, Azithromycin, and Hydroxychloroquine on QT Interval and Arrhythmic Risk in Hospitalized COVID-19 Patients - Vincenzo Russo; Andreina Carbone; Filiberto Fausto Mottola; Rosa Mocerino; Raffaele Verde; Emilio Attena; Nicoletta Verde; Pierpaolo Di Micco; Luigi Nunziata; Francesco Santelli; Gerardo Nigro; Sergio Severino (Frontiers Media S.A., 2020)
IntroductionNo data are provided about the effect of triple combination therapy with Lopinavir/Ritonavir (LPN/RTN), hydroxychloroquine (HQ) and azithromycin (AZT) on corrected QT (QTc) interval and arrhythmic risk, in COVID-19 patients. This study aims to describe the incidence of extreme QTc interval prolongation among COVID-19 patients on this experimental treatment and to identify the clinical features associated with extreme QTc prolongation.Materials and MethodsData of 87 COVID-19 patients, treated with triple combination including LPN/RTN, HQ and AZT, were analyzed. QT interval was obtained by the tangent method and corrected for heart rate using Bazett's formula. Extreme QTc interval prolongation was considered an absolute QTc interval ≥ 500 ms or an increase in QTc intervals of 60 ms or greater (ΔQTc ≥ 60 ms) compared with baseline.ResultsHypertension (66.7%) and diabetes (25.3%) were the most prevalent cardiovascular comorbidities. Twenty patients (23%) showed extreme QTc interval prolongation; no clinical, electrocardiographic or pharmacological characteristics have been associated to extreme QTc prolongation, except the history of ischemic stroke (P= 0,007). One torsade de pointes (TdP) in patient with QTc extreme prolongation (QTc: 560 ms) after 5 days of therapy was recorded.ConclusionsWe observed a high incidence of extreme QTc interval prolongation among COVID-19 patients on triple combination therapy. Since the incidence of malignant arrhythmias seems to be not negligible, a careful electrocardiographic monitoring would be advisable.